EVALUATION OF THE PSYCHOSOCIAL IMPACT OF DENTAL AESTHETICS BY SOCIODEMOGRAPHICS AND MALOCCLUSIONS - Kalender Muhammed Emin; Ucan Yarkac Fatma; Emiroglu Yunus (Romanian Journal of Oral Rehabilitation)
Aim of the study: This study evaluates the psychological and social effects of dental aesthetics in individuals aged 18–65 using the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Materials and Methods: A total of 407 people aged 18-65 participated in the study. Exclusion criteria included intellectual disabilities, craniofacial syndromes, ongoing orthodontic treatments, and psychological therapy. Sociodemographic data, oral hygiene habits, and dental aesthetics were assessed. Participants completed the PIDAQ survey with subscales for dental self-confidence, social impact, psychological impact, and aesthetic concern. Results: Dental self-confidence and social impact scores were significantly higher in the 18–34 age group compared to 35–64. Women scored higher in all subscales except dental self-confidence. Participants with malocclusions showed increased psychological and social impacts, regardless of malocclusion type (p<0.05). Discussion: Findings reveal significant psychosocial effects of dental aesthetics, varying by age, gender, and malocclusion status. Younger individuals and women reported greater concerns, likely influenced by societal expectations. These results align with previous studies but expand understanding by including a wider age range and malocclusion analysis.Conclusion: Dental aesthetics deeply influence self-confidence and social interactions, emphasizing the importance of addressing these concerns for both functional and psychological reasons. Further research should examine pre- and post-treatment effects to provide comprehensive insights.